Investigation of macrophage migration inhibitory factors and gene polymorphisms in patients with psoriasis - Vildan Manav; Seval Doğruk Kaçar; Pınar Özuğuz; Saliha Handan Yıldız; Müjgan Özdemir Erdoğan; Tülay Köken (Galenos Publishing House, 2021)
Background and Design: Psoriasis is a multifactorial disease whose causal origin is unclear. Macrophage migration inhibitory factors (MIF) seem pivotal in inflammation and immune response in psoriasis pathogenesis. We aimed to investigate the serum MIF levels and MIF gene polymorphism (rs755622 and rs1007888) in patients with psoriasis. Materials and Methods: In this study, the association of serum MIF levels and MIF gene polymorphisms with psoriasis were investigated among 100 patients in Turkey. Genotyping was performed by real-time polymerase chain reaction. Serum MIF levels were evaluated by ELISA, and the results were presented in ng/mL. Results: The distribution of rs755622 genotype frequencies in the psoriasis group was: 75, 18, and 4 patients with CC, CG, and GG, respectively. The distribution of rs1007888 genotype frequencies in the psoriasis group was: 22, 48, and 26 patients with AA, AG, and GG, respectively. There was no statistically significant difference between the two groups. However, there was a statistically significant difference between the mean serum MIF levels of psoriasis patients (3.29 ng/mL) compared with the control group (1.08 ng/mL) (p<0.001). Conclusion: Significantly higher serum MIF levels were found in patients with psoriasis. However, there was no gene polymorphism association for genetic markers rs755622 or rs1007888 with psoriasis. Further studies in larger populations are warranted to elucidate the role of MIF and its clinical effects.